2019
DOI: 10.4314/ajesms.v15i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Students’ conceptual understanding of electricity and magnetism and its implications: A review

Abstract: Physics subject continues to be considered as difficult and unattractive by students. This leads to the development of negative attitudes towards the subject. Electricity and magnetism as one of the most important areas in physics is particularly considered as difficult due to their abstract nature. Different studies on students’ conceptual understanding of electricity and magnetism have been conducted and several instructional strategies for a conceptual change in this subject matter have been provided. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Besides, many of the concepts of electricity and magnetism are abstract in nature in which they cannot be directly observed like those of velocity and acceleration of a moving car in mechanics (Li, 2012). Mbonyiryivuze et al (2019) also indicated that the mathematical formulas are a little bit complex to use them in solving problems in relation to electricity and magnetism. Therefore, from these natures of electricity and magnetism, there has to be a need of using students' prior knowledge and experience for the learning of new concepts and algorithms with a visualized manner for creating mental models through the use of active learning methods.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, many of the concepts of electricity and magnetism are abstract in nature in which they cannot be directly observed like those of velocity and acceleration of a moving car in mechanics (Li, 2012). Mbonyiryivuze et al (2019) also indicated that the mathematical formulas are a little bit complex to use them in solving problems in relation to electricity and magnetism. Therefore, from these natures of electricity and magnetism, there has to be a need of using students' prior knowledge and experience for the learning of new concepts and algorithms with a visualized manner for creating mental models through the use of active learning methods.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been noted that when asked solve problems in many poor countries, a large majority of students lack the requisite conceptual understanding. (Mbonyiryivuze. 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional teaching strategies which are usually teacher-centered have been claimed to be ineffective in developing students' conceptual understanding. Some studies reported that noticeable conceptual understanding change in learners after being taught using traditional teaching methods was short-lived (Mbonyiryivuze, 2019). A main concern for educational researchers and educators has been finding ways to improve current learning techniques to consequently improve students' conceptual understanding.…”
Section: Introductionmentioning
confidence: 99%
“…Processes of teaching and learning the concept of magnetic field have been objects of research throughout time and results point to huge difficulties due to teachers in teaching this content and students in learning it (Zuza, Van Kampen, de Cock, Kelly, & Guisasola, 2018;Mbonyiryivuze, Yadav & Amadalo, 2020;Zuza, Almudí, & Guisasola, 2012;Pantoja & Moreira, 2019b). The background does not seem to change from High School to Higher Education, including courses of teacher training.…”
Section: Introductionmentioning
confidence: 99%